2003
DOI: 10.1038/sj.bjc.6601398
|View full text |Cite
|
Sign up to set email alerts
|

Tissue microarray analyses of G1/S-regulatory proteins in ductal carcinoma in situ of the breast indicate that low cyclin D1 is associated with local recurrence

Abstract: Ductal carcinoma in situ (DCIS) of the breast constitutes about 10% of all diagnosed breast cancers and, despite surgical removal, it may recur, either as DCIS or invasive breast cancer. Nuclear grade and growth pattern according to Andersen et al as well as surgical margins are factors that have been used to predict local recurrence, but ideally a set of tumour-specific factors should be identified and used as prognostic markers. Many cell cycle regulatory gene products have been shown to be involved in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 32 publications
3
31
2
Order By: Relevance
“…Turner et al have investigated the influence of cyclin D1 protein expression on breast cancer recurrence in a case-matched study in 49 patients and found that low levels of immunohistochemically detected cyclin D1 protein correlated with LR [29]. Also, in DCIS, low levels of cyclin D1 protein expression were associated with local recurrence [30]. As has been suggested before, these different findings from our study may be explained by different antibodies for cyclin D1 and methods of detection.…”
Section: Discussioncontrasting
confidence: 54%
“…Turner et al have investigated the influence of cyclin D1 protein expression on breast cancer recurrence in a case-matched study in 49 patients and found that low levels of immunohistochemically detected cyclin D1 protein correlated with LR [29]. Also, in DCIS, low levels of cyclin D1 protein expression were associated with local recurrence [30]. As has been suggested before, these different findings from our study may be explained by different antibodies for cyclin D1 and methods of detection.…”
Section: Discussioncontrasting
confidence: 54%
“…The beneficial effect of cyclin D1 overexpression on breast cancer survival was also reported by several others groups (15)(16)(17)(18)(19)(20). Notably, a study using microarray analysis of cyclin D1 expression reported that high cyclin D1 expression was associated with low risk of local recurrence of breast cancer, whereas low expression was associated with high risk (16).…”
Section: Introductionmentioning
confidence: 71%
“…Notably, a study using microarray analysis of cyclin D1 expression reported that high cyclin D1 expression was associated with low risk of local recurrence of breast cancer, whereas low expression was associated with high risk (16). The other studies showed that strong staining of cyclin D1 is associated with inverse tumor grade, smaller tumor size, and improved relapse-free and overall survival of breast cancer patients (18,20).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a positive correlation between cyclin D1 expression and aggressive cancers, as documented above, there is evidence to suggest otherwise as well. For example, a study using microarray analysis of cyclin D1 expression identified high cyclin D1 expression as a low risk factor for local recurrence of breast cancer (Jirstrom et al, 2003). Low expression of cyclin D1 expression was, conversely, associated with high risk of cancer recurrence.…”
Section: Cell Cycle Regulation In Tamoxifen Resistant Breast Cancersmentioning
confidence: 99%